The Modified Impact of CEO Characteristics on the Relationship Between Internal Audit Quality and Firms Performance in The Jordanian Corporations - Magablih, Ali Mustafa (Journal of Public Administration and Governance, 2023)
The study aim to identify the modified impact of the characteristics of the CEO on the relationship between the quality of internal auditing and the performance of the Jordanian corporations. The study population consisted of Jordanian corporations listed on Amman stock exchange. In order to achieve the objective of the study they adopted the descriptive analytical approach, by developing the questionnaire that was distributed. The study populations consist of all Jordanian corporations and 250 questioners was distributed in the study sample consisting of financial manager, internal auditor and heads of accounting department 206 questionnaire were received of which 183 were valid for analysis. Used the SPSS program in analysis the study tool in addition to some descriptive statistical methods (arithmetic, means and standard deviation). The study reached a number of results , most important of which are there is statistically significance level the quality of internal audit and positively effect the performance of Jordanian corporations, in addition the characteristic of the CEO passively effect the reaction ship between the quality of internal auditing and the performance of the Jordanian corporations. The study also came out with a number of recommendations, the most important of which were the need to strength and improving the internal audit function in Jordanian companies, increasing its quality, and focusing more on the characteristics and attributes of the CEO. As well as the need for companies to keep abreast of developments and techniques related to internal auditing and use them in internal audit operations in Jordanian corporations.